Methylmercury formation in biofilms of Geobacter sulfurreducens - Yunda, Elena; Gutensohn, Mareike; Ramstedt, Madeleine; Björn, Erik (Frontiers in Microbiology, 2023)
Introduction Mercury (Hg) is a major environmental pollutant that accumulates in biota predominantly in the form of methylmercury (MeHg). Surface-associated microbial communities (biofilms) represent an important source of MeHg in natural aquatic systems. In this work, we report MeHg formation in biofilms of the iron-reducing bacterium Geobacter sulfurreducens. Methods Biofilms were prepared in media with varied nutrient load for 3, 5, or 7 days, and their structural properties were characterized using confocal laser scanning microscopy, cryo-scanning electron microscopy and Fourier-transform infrared spectroscopy. Results Biofilms cultivated for 3 days with vitamins in the medium had the highest surface coverage, and they also contained abundant extracellular matrix. Using 3 and 7-days-old biofilms, we demonstrate that G. sulfurreducens biofilms prepared in media with various nutrient load produce MeHg, of which a significant portion is released to the surrounding medium. The Hg methylation rate constant determined in 6-h assays in a low-nutrient assay medium with 3-days-old biofilms was 3.9 ± 2.0 ∙ 10−14 L ∙ cell−1 ∙ h−1, which is three to five times lower than the rates found in assays with planktonic cultures of G. sulfurreducens in this and previous studies. The fraction of MeHg of total Hg within the biofilms was, however, remarkably high (close to 50%), and medium/biofilm partitioning of inorganic Hg (Hg(II)) indicated low accumulation of Hg(II) in biofilms. Discussion These findings suggest a high Hg(II) methylation capacity of G. sulfurreducens biofilms and that Hg(II) transfer to the biofilm is the rate-limiting step for MeHg formation in this systems.